Multilingual Crisis Communication Beyond Translation: Canadian Lessons from the Pandemic - Córdoba Serrano, María (TTR, 2025)
This article presents a case study that examines multilingual communication practices in Canada’s Indigenous and non-official languages, as facilitated by Indigenous Services Canada (ISC) and the Public Health Agency of Canada (PHAC) during the COVID-19 pandemic. Despite a lack of reliable language-related data and the absence of a multilingual crisis communication policy framework, these two federal entities integrated a multilingual lens into their multipronged communication strategy, which included but was not limited to translating critical information. Their communication strategy resulted not only in information on a wide range of topics being available in an unprecedented number of languages/dialects, but also in the emergence of bottom-up multilingual communication practices, developed in collaboration with community-based organizations and Indigenous governments, that served to build trust and effect behavioural change. The article further argues that the emergence of these practices can help us to rethink language management in Canada in general and redefine the roles that translation and translators might play in multilingual digital communication, particularly in the age of multilingual artificial intelligence (AI), when language professionals are expected to renegotiate and broaden their professional mandates (Slator, 2024).